Engineering methods and software support for modeling and design of discrete-time control of distributed parameter systems - Hulko, G.; Belavy, C.; Meszaros, A.; Bucek, P.; Ondrejkovic, K.; Zajicek, P. (ECC : 2009 European Control Conference : 23-26 August 2009, 2009)
In this mini-tutorial some advanced engineering methods are presented for modeling and design of discrete-time control of distributed parameter systems described for control purposes by numerical structures over complex-shape 3D definition domains along with the software package Distributed Parameter Systems Blockset for MATLAB & Simulink - Third-Party MathWorks product, inspired by the boom of numerical analysis of dynamics of machines and processes within engineering practice. The techniques offered are completed by a user-friendly Web service tool, suitable for interactive solution of model control problems of distributed parameter systems via the Internet.